Short-Term Outcome of Septoplasty With or Without Nasal Packing - Sharif, Sayed Muhammad Alauddin; U, K Khin; Chowdhury, Pankaj Kumer; Faruquee, Mahmud Ullah; Chakma, Mitan; Arifuzzaman, Md; Biswas, Supran; Chakma, Pradipta (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Although there is recommendation for the avoidance of packing following septoplasty, it has been practiced in our setting to avoid complications like bleeding and septal hematoma, probably due to lacking of a genuinely randomized study to justify this recommendation in our setting. This study evaluated the short-term outcome of septoplasty with or without anterior nasal packing in patients with symptomatic Deviated Nasal Septum (DNS). Materials and methods: Sixty patients with DNS aged 18-40 were enrolled in this study and were randomly allocated into two groups: 30 Underwent Nasal Packing (NPG) and 30 did not follow septoplasty. In the no- packing group, trans-septal Quilting Suturing was done (QSG). Visual Analogue Scale and Nasal Obstruction Symptoms Evaluation (NOSE) scale were used to record pain and obstruction symptoms in the postoperative period up to 1-month following septoplasty. Results: All patients reported a reduction of NOSE score, with a non-significant difference between both groups at one month (p=0.056). Patients in the NPG reported higher pain scores than the QSG group in the first 24 hours (8.30±0.53 vs. 3.60 ±0.68, p<0.001) and one week after surgery (6.00±1.34 vs. 1.87±1.96, p<0.001). Epiphora, headache, dysphagia and crust formation were also more commonly observed in NPG. Conclusion: This study confirmed that packing of nose is unnecessary following septoplasty and is a source of discomfort for the patients. JCMCTA 2024 ; 35 (2) : 130-134